2020
DOI: 10.22437/jmj.v8i1.9489
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Pasien Efusi Pleura Di Kota Jambi

Abstract: ABSTRACT Introduction Pleural effusion is a condition where the fluid either a transudate or an exudate accumulate in pleural cavity. Disease that can cause pleural effusion can be either a malignancy or an inflammatory process. Intratoracal and extratoracal malignancies can cause pleural effusion (malignant pleural effusion / MPE). The aim of this study was to describe the characteristics of patients with pleural effusion and the proportion of malignant pleural effusion in Jambi City. Methods This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…Gender plays a significant role in a person's quality of life, with men being the most affected by pleural effusion. This is consistent with research conducted in Jambi City, indicating a higher percentage in men compared to women (63.77%) (Adeoye et al, 2017;Dewi & Fairuz, 2020;Khilar & S., 2023). Additional studies support the notion that men have a higher incidence of pleural effusion, especially due to pulmonary tuberculosis, with a percentage of 64.9% (Ampow et al, 2023).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Gender plays a significant role in a person's quality of life, with men being the most affected by pleural effusion. This is consistent with research conducted in Jambi City, indicating a higher percentage in men compared to women (63.77%) (Adeoye et al, 2017;Dewi & Fairuz, 2020;Khilar & S., 2023). Additional studies support the notion that men have a higher incidence of pleural effusion, especially due to pulmonary tuberculosis, with a percentage of 64.9% (Ampow et al, 2023).…”
Section: Discussionsupporting
confidence: 90%
“…Pleural effusion is frequently observed in individuals aged 40 to 59 years. Research results indicate that 50.72% of cases occurred within this age group (Dewi & Fairuz, 2020). Another study found that the age group 40 to 59 years had the highest prevalence of pleural effusion, accounting for 58.3% of cases (Hutagalung et al, 2022).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Lebih dari 75% Efusi Pleura disebabkan oleh keganasan di paru, payudara, atau ovarium, serta limfoma. (Dewi et al, 2020) Efusi pleura dapat berupa penyebaran dari keganasan yang merupakan manifestasi awal dari keganasan intra atau ekstratoraks yang mendasarinya. Penyebaran langsung sel-sel ganas, invasi dari vaskularisasi paru dengan embolisasi dari sel-sel tumor ke pleura viseralis, atau metastasis jauh hematogen dari tumor ke pleura parietalis.…”
Section: Pendahuluanunclassified
“…Pleural effusion is a condition where fluid accumulates in the pleural cavity in abnormal amounts, either as a result of pleural membrane transudation or excessive exudation as a difficulty arising from multiple medical conditions (Khairani, Syahruddin, and Partakusuma, 2012). Infectious diseases such as tuberculosis, pneumonia, and abscesses, as well as non-infectious diseases such as carcinoma, kidney failure, and pulmonary embolism, can cause pleural effusion (Dewi and Fairuz, 2020). Cases of pleural effusion in the United States are reported to reach 1-1.5 million new cases each year.…”
Section: Introductionmentioning
confidence: 99%